Evaluation of podofilotoxina 0,15% for treatmentof HPV lesions - Dias, Maria Fernanda RG; Sá, Ricardo P; Sampaio, Felipe MS; Machado, Pedro V; Miller, William M; Kadi, Nadia T; Nery, José Augusto C (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: condylomata acuminata is provoked by Human Papillomavirus (HPV), of which there are more than 100 different types. It ́s believed that is afactor that facilitates sexual transmission of Human immunodeficiency virus (HIV) making early diagnosis and treatment of HPV of great importance.Trichloroacetic acid (TCA 90%) and electrocauterization are the two most common forms of treatment, however both are painful and require a specializedphysician. Podophyllin 25% solution is often used, but because of its unstable character it expires quickly. Objective: study the domiciliary use of podofilotoxinacream 0.15%, the active substance of podophyllin resin, chemically stable, inhibits cellular division, and is an antiviral drug with antimitotic properties thatcan be self-administered. It ́s considered painless when compared to other forms of treatment. Methods: patients were instructed to apply the medication twicea day, three times a week for a maximum of four weeks, and the lesions were counted during a consultation after each cycle. Results: A statistical analysisshowed a significant reduction in the number of lesions over the course of treatment. The lesion count at the first consultation compared with that after the firstcycle and after the fourth cycle resulted in a p-value of 0.001134 and 0.000699, respectively. After the completion of treatment, cure was observed in 72%,improvement in 15%, and no change in 13% of the patients. Conclusion: the auto-application of podofilotoxina cream 0.15% for the treatment of condylomataacuminata proved to be an effective method, with the advantage of reducing the necessary time to treat the patient in the private or public sector and notprovoking pain.